Effects Of Combination Sunkist and Lime Peel Nanoparticle Granules on Oxidative Stress and Heart Histopathology in Diabetes Rats - Sihotang, Widya Yanti; Mutia, Maya Sari; Chairul, Muhammad; Irwanda, Desi Danilah; Nabila, Putri; Hamsi, Ulpah Zahara (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
Diabetes mellitus and its consequences are significantly influenced by oxidative stress. Sunkist and lime oranges are a nutritional powerhouse, offering a range of health benefits due to their high content of antioxidants, vitamins, minerals, and fiber. Key compounds like anthocyanins, flavanones, and hydroxycinnamic acid contribute to their potential positive impact to reduce oxidative stress. Therefore, the effect of nanoparticle granules combination of sunkist orange peel and lime peel was investigated on diabetic rats. Twenty male Wistar rats were randomly distributed:  Group 1 as control group given distilled water, Group 2 as DM group with alloxan, Group 3 with DM + NGSLP 100mg / kgBW, Group 4 with DM + NGSLP 200mg / kgBW. Rats with diabetes were treated by intraperitoneal injection with 100 mg/kg alloxan. NGSLP treatment was given for 14 days to each treatment group. At the end, the blood and heart tissue were collected and used to determine the GPx enzyme, SOD, MDA, CAT and histological evaluation. Diabetes induction increased the level of MDA and decreased after treated with NGSLP. In diabetic rats treated with NGSLP showed an increase in SOD, GPX and CAT in blood. Histopathological findings of heart tissue showed the protective effect of NGSLP in rats with diabetic. This study revealed that NGSLP has antioxidant effects in the blood and heart of alloxan-induced diabetic rats.